KAJIAN AGRIBISNIS TAHU (Studi Kasus di Kabupaten Biak Numfor) - I Made Suaryadana; Eri Yusnita Arvianti (BUANA SAINS, 2008)
A study that was aimed to describe financial feasibility of tofu home industry development in Biak Numfor Regency has been conducted from October to December 2008. The existing six tofu home industries in Biak Numfor Regency were subjected for this study. Results of the study showed that the average production capacity of tofu home industry in Biak Numfor Regency was 163.093 ton/year. This was based an assumption that one year is 365 days, the average production was 1.162.182 pieces. Production capacity was recorded to be 1.173.077 - 1.233.658 pieces and raw material need was 120.651 -126.882 ton / year. Labours used for tofu processing ranged from 5-6 persons with salary of Rp. 1.200.000/month/person. Own capital spent for tofu production was Rp. 1.689.700.000,- per year. Tofu producers could make profits when they could produce at least 470.941 pieces/year at a price of Rp. 2.000,- / piece. Based on the average total production for 5 years of 941.881.225 pieces with total production cost of Rp 1.233.658, the price BEP was 763,49. Considering to the B/C ratio value of 2,62, the tofu home industry was feasible for further development. Investment of tofu home industry was also feasible. This was based on the discount rate of 16%, the NPV value of Rp 967.206.279,- form the present value of Rp 995.385 542,- with investment value of Rp. 28.179.262. This indicated that tofu home industry was feasible for further development in Biak Numfor Regency